An Overview of Atmospheric Features Over the Western North Atlantic Ocean and North American East Coast—Part 2: Circulation, Boundary Layer, and Clouds. Issue 6 (17th March 2021) - Painemal, David; Corral, Andrea F.; Sorooshian, Armin; Brunke, Michael A.; Chellappan, Seethala; Afzali Gorooh, Vesta; Ham, Seung‐Hee; O'Neill, Larry; Smith, William L.; Tselioudis, George; Wang, Hailong; Zeng, Xubin; et al.
Abstract: The Western North Atlantic Ocean (WNAO) is a complex land‐ocean‐atmosphere system that experiences a broad range of atmospheric phenomena, which in turn drive unique aerosol transport pathways, cloud morphologies, and boundary layer variability. This work, Part 2 of a 2‐part paper series, provides an overview of the atmospheric circulation, boundary layer variability, three‐dimensional cloud structure, and precipitation over the WNAO; the companion paper (Part 1) focused on chemical characterization of aerosols, gases, and wet deposition. Seasonal changes in atmospheric circulation and sea surface temperature explain a clear transition in cloud morphologies from small shallow cumulus clouds, convective clouds, and tropical storms in summer, to stratus/stratocumulus and multilayer cloud systems associated with winter storms. Synoptic variability in cloud fields is estimated using satellite‐based weather states, and the role of postfrontal conditions (cold‐air outbreaks) in the development of stratiform clouds is further analyzed. Precipitation is persistent over the ocean, with a regional peak over the Gulf Stream path, where offshore sea surface temperature gradients are large and surface fluxes reach a regional peak. Satellite data show a clear annual cycle in cloud droplet number concentration with maxima (minima) along the coast in winter (summer), suggesting a marked annual cycle in aerosol‐cloud interactions. Compared with satellite cloud retrievals, four climate models qualitatively reproduce the annual cycle in cloud cover and liquid water path, but with large discrepancies across models, especially in the extratropics. The paper concludes with a summary of outstanding issues and recommendations for future work. Key Points: Atmospheric circulation and sea surface temperature drive large seasonal changes in precipitation, surface fluxes, and cloud types Synoptic activity in winter yields the highest seasonal rain rates, low‐cloud occurrence, and cloud droplet number concentrations Climate models simulate a wide range of low‐cloud properties, with improved results for models with more sophisticated turbulence schemes